Tensile properties of pineapple leaf fibre reinforced unsaturated polyester composites - Siregar, Januar Parlaungan; Cionita, Tezara; Bachtiar, Dandi; Mohd Ruzaimi, Mat Rejab (Trans Tech Publications Ltd, 2015)
In recent years natural fibres such as sisal, jute, kenaf, pineapple leaf and banana fibres appear to be the outstanding materials which come as the viable and abundant substitute for the expensive and non-renewable synthethic fibre. This paper investigate the effect of fibre length and fibre content on the tensile properties of pineapple leaf fibre (PALF) reinforced unsaturated polyester (UP) composites. PALF as reinforcement agent will be employed with UP to form composite material specimens. The various of fiber length (<0.5, 0.5–1, and 1-2 mm) and fibre content (0, 5, 10 and 15 % by volume) in UP composite have been studied. The fabrication of PALF/UP composites used hand lay-up process, and the specimens for tensile test prepared follow the ASTM D3039. The result obtained from this study show that the 1-2 mm fibre length has higher tensile strength (42 MPa) and tensile modulus (1344 MPa) values compared to fibre length of <0.5 mm (30 MPa and 981 MPa) and 0.5-1 mm (35.40 MPa and 1020 MPa) respectively. Meanwhile, for the effect of various fibre content in study has shown that the increase of fibre content has decreased in tensile strength dan tensile modulus of composites. The increase of fibre content due to poor interfacial bonding and poor wetting of the fibre by unsaturated polyster. The treatment of natural fibre are suggested in order to improve the interfacial adhesion between natural fibre and the unsaturated polyester.